Trace Minerals and Livestock: Not Too Much Not Too Little. (4th December 2012) - López-Alonso, Marta
Abstract : The new approaches of the animal production systems make managing the mineral nutrition a challenge. Versus the excessive, trace mineral supply in intensively managed livestock, well above the physiological requirements, is the no trace mineral supplementation of organic systems, which become highly dependent on trace minerals in the soil. Nowadays, in addition to the animal health perspective, trace mineral nutrition must be environment friendly and allow getting mineral-enriched animal products. We are in a new scenario, where a balance between animal trace mineral needs and limits is needed. This papers focuses on different aspects that will help us to enter a critical dialogue in relation to animal-human-environment.